A new species of the Dendropsophus parviceps group from the western Amazon Basin (Amphibia: Anura: Hylidae) - Motta, Ana P.; Castroviejo-Fisher, Santiago; Venegas, Pablo J.; Orrico, Victor G.d.; Padial, José M. (Zootaxa, 2012)
We describe Dendropsophus frosti sp. nov. from lowland terra firme rainforests of the headwaters of the Amazon RiverBasin in Colombia and Peru. The new species is known from only two localities, the type locality near Leticia (Departa-mento Amazonas, Colombia, 04° 06’ 24.2" S, 69° 56’ 57.4" W; 103 m.a.s.l.), and the paratopotypic locality, Piedras in thePutumayo basin (Departamento Loreto, Peru, 02.79278° S, 72.91750° W; 90–170 m.a.s.l.). Maximum likelihood and par-simony analyses of 2436 aligned base pairs of the 12S and 16S rRNA genes recovered the new species as a member of D.parviceps group and sister to D. brevifrons. The new species is most closely related to D. parviceps, D. brevifrons, and D.koechlini, and it can be readily distinguished from these and all other members of the D. parviceps group by, among othercharacters, its plain dorsal light brown coloration, copper iris, plain immaculate pale yellow to white venter coloration, lack of flash marks on groin and axillae, and absence of white spots on lips.